2019
DOI: 10.21041/ra.v9i2.335
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between water absorption, electrical resistivity and compressive strength of concrete with different contents of pozzolan

Abstract: This research confronts the following concrete properties: water absorptions (by immersion and capillarity), electrical resistivity and compressive strength. Concrete mixtures with two types of cement were tested. Results showed that concretes with higher content of pozzolan had higher resistivity and greater absorption by capillarity, for water/cement ratios lower than 0,60. This behavior is attributed to reduced pore diameters and microstructure densification. However, for water/cement ratio of 0,60, concret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 25 publications
(37 reference statements)
2
13
1
3
Order By: Relevance
“…Partial replacement of cement with PSBE reduces water absorption rate because the pozzolanic reaction of PSBE produces secondary hydration which increases the amount of hydration product [ 43 ]. An increase in hydration product results in smaller internal pores and a denser mortar microstructure which can resist the penetration of water and other aggressive substances [ 44 ]. Moreover, fine PSBE particle can serve as a filler of mortar and enhance the space filling properties of the paste.…”
Section: Resultsmentioning
confidence: 99%
“…Partial replacement of cement with PSBE reduces water absorption rate because the pozzolanic reaction of PSBE produces secondary hydration which increases the amount of hydration product [ 43 ]. An increase in hydration product results in smaller internal pores and a denser mortar microstructure which can resist the penetration of water and other aggressive substances [ 44 ]. Moreover, fine PSBE particle can serve as a filler of mortar and enhance the space filling properties of the paste.…”
Section: Resultsmentioning
confidence: 99%
“…Capillary water absorption is usually related with the diffusivity of aggressive ions into the concrete trough the porous structure [62], consequently it is used as a parameter to assess the adequacy of a mix exposed to a specific environment. In this research it has been observed that the addition of SCB FA increase the capillary absorption when compared with the control concrete but, in contrast, the chloride migration is reduced, and no direct correlation exists, Figure 24(e).…”
Section: Capillary Absorptionmentioning
confidence: 99%
“…Os resultados obtidos para a capacidade de absorção de água dos concretos estão em concordância com os valores de resistência à compressão axial obtida para os concretos produzidos. Em geral, um aumento na capacidade de absorção de água, implica uma redução da resistência à compressão e um aumento na porosidade [52,54]. A maior absorção de água obtida para o concreto 10-PET pode ser atribuído a um aumento na porosidade do material.…”
Section: Absorção De áGuaunclassified